Efficacy, expectancy, or the sense of mattering? Academic procrastination in online study - Hong Chun Yeoh; Susanna Poay Lin Hong; Kususanto Ditto Prihadi (International Journal of Evaluation and Research in Education (IJERE), 2022)
Past studies reported that academic procrastination (AP) was contingent upon students’ educational self-efficacy (ASE) and the expectancy-value belief (EV), which were developed through social interaction. When teaching and learning in most universities were altered into online learning (OL) during the pandemic, students’ social interaction was more inclined toward online communication, especially through social networking sites (SNS); a phenomenon that has been reported to alter their sense of societal mattering (SM), the sense that they matter to the society. We hypothesized that SM moderates the mediation of EV on the association between ASE and AP. We purposively recruited 361 university students who must study fully online from home during the outbreak and asked them to respond to the designated scales. The bootstrap analysis with 5,000 samples and a 95% confidence interval showed that the moderated mediation hypothesis was supported. Students who believe that they can perform well tend to value their tasks higher, and therefore had a lower rate of procrastination. However, this mediation did not occur among students who do not think that they matter enough to the university as a society.